The pan-immune-inflammation value is associated with clinical outcomes in patients with advanced TNBC treated with first-line, platinum-based chemotherapy: an institutional retrospective analysis - Leonardo Provenzano; Riccardo Lobefaro; Francesca Ligorio; Emma Zattarin; Luca Zambelli; Caterina Sposetti; Daniele Presti; Giulia Montelatici; Angela Ficchì; Antonia Martinetti; Alessio Arata; Marta Del Vecchio; et al. (Therapeutic Advances in Medical Oncology, 2023)
Background: Advanced triple-negative breast cancer (aTNBC) has a poor prognosis; thus, there is a need to identify novel biomarkers to guide future research and improve clinical outcomes. Objectives: We tested the prognostic ability of an emerging, complete blood count (CBC)-based inflammatory biomarker, the pan-immune-inflammation value (PIV), in patients with aTNBC treated with first-line, platinum-based chemotherapy. Design: This was a retrospective, monocentric, observational study. Methods: We included consecutive aTNBC patients treated with platinum-based, first-line chemotherapy at our Institution, and for whom baseline (C1) CBC data were available. We collected CBC data early on-treatment, when available. PIV was calculated as: (neutrophil count × platelet count × monocyte count)/lymphocyte count. Patients with hormone receptor-positive (HR+), human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer (aBC) were included in a control, non-TNBC cohort. Results: A total of 78 aTNBC patients were included. When evaluated as a continuous variable, PIV-C1 was associated with worse overall survival (OS; p  < 0.001) and progression-free survival (PFS; p  < 0.001). On the other hand, when PIV-C1 was assessed on the basis of its quantile distribution, patients with ‘high PIV-C1’ experienced worse OS [adjusted hazard ratio (HR): 4.46, 95% confidence interval (CI): 2.22–8.99; adjusted p  < 0.001] and PFS (adjusted HR: 2.03, 95% CI: 1.08–3.80; adjusted p  = 0.027) when compared to patients with ‘low PIV-C1’. Higher PIV-C1 was also associated with primary resistance to chemotherapy. Similarly, a higher PIV calculated from CBC at C2D1 (PIV-C2) was associated with worse survival outcomes. We also created a PIV-based score combining information about both PIV-C1 and PIV-C2 and allowing the stratification of patients at low, intermediate, and high risk of death. No association was observed between PIV-C1 and clinical outcomes of HR+/HER2− aBC patients. Conclusion: PIV has a promising prognostic discrimination ability in aTNBC patients treated with first-line, platinum-based chemotherapy. Both baseline and early on-treatment PIV are associated with clinical outcomes and may be exploited for creating PIV-based risk classifiers if further validated.